Information Literacy Beyond Librarians: A Data/Methods Triangulation Approach to Investigating Disciplinary IL Teaching Practices - Foster, Britt (Evidence Based Library and Information Practice, 2020)
Objective – While library literature contains many studies examining faculty perceptions of the value of librarian-led information literacy (IL)instruction, there is little evidence regarding IL instruction practices of disciplinary faculty independent of librarians. In a climate of uncertain budgets, increasing student enrollment, and increased conversation around the need for IL, media, and digital literacy skills, this study aimed to investigate a little-researched area of the IL instruction, learning, and development milieu.Methods – In collaboration with the institutional research office, a data and methods triangulation approach was used. A survey of disciplinary faculty was administered and disciplinary faculty focus groups were also conducted. Student outcomes and annual assessment reports, documents that describe teaching and assessment methods for courses across the university, were analyzed. Voyant, a text-mining tool, was also used to determine key phrases and terms related to IL in these documents.Results – Results revealed that disciplinary faculty highly value skills and understandings affiliated with IL competency. Faculty provide the majority of IL learning opportunities independent of librarians, although these learning opportunities are generally provided through implicit, rather than explicit, methods. Pedagogical methods that may enable explicit practices, such as the use of standards and competencies, are infrequently used.Conclusion – Evidence and findings from this study are being used to inform several initiatives to work with disciplinary faculty for IL instruction, including new services, resources, and instruction models to support IL development in students.